2011
DOI: 10.1590/s1413-81232011000500026
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência e fatores associados à obesidade em mulheres usuárias de serviços de pronto-atendimento do Sistema Único de Saúde no sul do Brasil

Abstract: A obesidade é uma das principais epidemias modernas, sendo importante problema de saúde pública e estando associado a um aumento de doenças crônicas. O objetivo deste estudo é investigar a prevalência de sobrepeso e obesidade e seus fatores associados em mulheres de 20 a 59 anos, usuárias de serviços de pronto atendimento do Sistema Único de Saúde. Realizou-se entrevista padronizada e foram tomadas as medidas antropométricas em 440 mulheres. O modelo de Poisson foi usado para avaliar a associação entre obesida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
1
15

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 12 publications
3
9
1
15
Order By: Relevance
“…The findings are close to those observed in other world cities, such as in Gaziantep, Turkey (33.7 percent) (5) and West Virginia (25 percent) (14) , as well as in some Brazilian cities, such as Criciúma (SC -34.1 percent) (15) and Santarém (PA -32.8 percent) (16) .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The findings are close to those observed in other world cities, such as in Gaziantep, Turkey (33.7 percent) (5) and West Virginia (25 percent) (14) , as well as in some Brazilian cities, such as Criciúma (SC -34.1 percent) (15) and Santarém (PA -32.8 percent) (16) .…”
Section: Discussionsupporting
confidence: 86%
“…However, a Brazilian investigation showed the highest prevalence of overweight women was observed among women with lower levels of education (4) . The average age of the sample participants was 40.85 ± 11.22 years, which was similar to those in a survey conducted in Criciúma, Santa Catarina between 2006 and 2007 (42 ± 12 years) (15) .…”
Section: Discussionsupporting
confidence: 79%
“…52.6% of men and 44.1% of women 6 . Studies have identified the sedentary lifestyle, smoking, unhealthy eating habits, reproductive history for women, alcohol intake, socioeconomic conditions and genetic factors as factors associated with the occurrence of obesity and/or overweight in different populations [7][8][9][10][11] . resumO: Estudo transversal para investigar a prevalência de obesidade, excesso de peso e obesidade abdominal, e a associação com o nível de prática de atividade física (AF), mensurada segundo o Internacional Physical Activity Questionnaire (IPAQ), em funcionários de uma universidade do Rio de Janeiro.…”
Section: Introductionmentioning
confidence: 99%
“…Em estudo realizado no Brasil nas regiões Nordeste e Sudeste, observou-se que mais da metade das mulheres dessas regiões com idade entre 40 e 79 anos têm sobrepeso 22 . Em 2011, no Sul do Brasil, verificou-se que a prevalência de sobrepeso e obesidade (64,3%) e de obesidade central (44,1%) em usuárias de serviços do SUS é maior do que a encontrada na população geral e está associada a um aumento do número de agravos à saúde 23 . Segundo os dados da WHO, 59% das mulheres brasileiras encontram-se acima do peso normal (sobrepeso ou obesidade).…”
Section: Discussionunclassified